Proceedings of the 10th Koli Calling International Conference on Computing Education Research 2010
DOI: 10.1145/1930464.1930466
|View full text |Cite
|
Sign up to set email alerts
|

Exploring suggestions for improving a computing course

Abstract: The purpose of this study was to understand teachers' perceptions about possible course improvements based on students' suggestions. The course involves a software development project of median complexity. In this study the Q-methodology was used as the research methodology. Suggestions of possible improvements were collected from the students of the course and used as a concourse. A sample of the concourse was presented to the teachers, who rank-ordered them according a predefined scale and, next, data was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…However, where Q-Methodology has been used in computing education research, it has been shown to provide detailed and useful insights into improving computing education and educational practice. For instance, see [1][2][3][4][5]. This poster will therefore explore the use of Q-Methodology within computing education research and identify how it can be used to aid researchers in future work.…”
Section: Q-methodologyincomputing Educationresearchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, where Q-Methodology has been used in computing education research, it has been shown to provide detailed and useful insights into improving computing education and educational practice. For instance, see [1][2][3][4][5]. This poster will therefore explore the use of Q-Methodology within computing education research and identify how it can be used to aid researchers in future work.…”
Section: Q-methodologyincomputing Educationresearchmentioning
confidence: 99%
“…students, teachers, course leaders) could be grouped together within Q-Methodology. This could prove valuable when conducting computing education research, as due to the pace of change, initiatives to improve computing courses should involve teacher and student views [4]. Q-Methodology involves:…”
Section: Introductionmentioning
confidence: 99%